Radiographic evaluation of the technical quality of root canal filling in Riyadh government and private hospitals - Mohammad I Al-Obaida; Khaled M Alwehaiby; Omar H Al-Hindi; Khalid Merdad; Ebtissam M Al-Madi (Wolters Kluwer Medknow Publications, 2020)
Introduction: The aim of this study is to evaluate radiographically the quality of root filling in endodontically treated teeth among a Riyadh population in governmental and private hospitals. Materials and Methods: Four hundred radiographs or obturated root canals in government and private hospitals were evaluated with regard to length, taper, and density of the root canal filling. The criterion-based number of adequate fill was identified and the root canal obturations were categorized as adequate or inadequate. Results: There were a statistically significant higher percentage of adequately obturated root canals in terms of length, density, and taper in government hospitals as compared to private hospitals. Moreover, the proportion of adequate length and taper of root canal was significantly higher in anterior teeth when compared with premolar and molar teeth in both private and governmental hospitals. There was no statistically significant association between the assessment of density of root canal and the type of tooth. Conclusion: The overall quality of the root canal filling in endodontically treated teeth in governmental hospitals was higher than in private hospitals and higher than some reported studies around the world.